Hubungan Asupan Serat dengan Status Gizi pada Peserta Prolanis Puskesmas Kedaton Bandar Lampung - Sutrio Sutrio; Arie Nugroho; Endang Sri Wahyuni; Anggun Rusyantia; Mindo Lupiana (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
The Chronic Disease Management Program (Prolanis) is a healthcare service program aimed at improving the quality of life of individuals with chronic diseases. Fiber intake plays a crucial role in maintaining optimal nutritional status, especially for individuals with diabetes and hypertension, who are the main targets of Prolanis. This study aims to examine the relationship between fiber intake and nutritional status among Prolanis participants at Kedaton Community Health Center (Puskesmas Kedaton). The research employed a descriptive-analytic design with a cross-sectional approach. A total of 60 respondents were selected using purposive sampling. Fiber intake data were obtained through a 2x24-hour food recall, while nutritional status was determined using Body Mass Index (BMI) measurements. Data analysis was conducted using the Chi-square test. The results showed that nearly half of the Prolanis participants had inadequate fiber intake (47.6%) and excessive nutritional status (50%). Statistical tests revealed a significant relationship between fiber intake and nutritional status (p = 0.005). Strengthening nutrition education for Prolanis participants is necessary, particularly regarding the importance of daily fiber consumption as part of chronic disease management and nutritional status maintenance to help control body weight and improve nutritional outcomes.